Active–reactive coordinated voltage regulation for rural distribution network considering demand response of large-scale aquaculture - Jifan Zhang; Wangqing Mao; Taibao Xia; Jun Zhuang; Xiaoliang Li; Deshun Wang (Frontiers in Energy Research)
The deepening of rural revitalization has diversified the development of rural economic industries and led to the rapid growth of energy demand. However, the infrastructure of the rural distribution network is relatively weak, and voltage fluctuations are becoming increasingly severe, posing huge challenges to the operational safety and stability of the distribution network. This study presents an active-reactive coordinated voltage regulation strategy for a rural distribution network with large-scale aquaculture activity by considering approaches that include distributed energy generation, energy storage, static var generators, and demand response (DR) of the aquaculture load. The proposed approach involves construction of a DR model for aquaculture equipment based on energy demand and operational characteristics. Accordingly, a voltage regulation optimization model is established with the goal of minimizing voltage fluctuations at the nodes of the distribution network by solving the weighted mean of vectors algorithm. Finally, a case study is used to verify the effectiveness of the proposed voltage regulation strategy, which is of great significance for promoting the development of rural distribution networks and economic industries.